Practices of Sustainable Development at Elementary Schools Level: What Research Says? - et. al., Ms. Aishwarya Swain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper is the outcome of a study conducted to find out academic and non-academic activities performed in schools to promote Education for Sustainable Development (ESD) based on environmental, social and economic sustainability. It tried to find out various initiatives undertaken by teachers to promote ESD. Descriptive survey design was adopted in this study. Forty (N=40) randomly selected teachers from 12 elementary schools comprised the sample of the study. A self-developed open-ended questionnaire was administered to teachers for collection of data. Data were analyzed qualitatively through thick description. Percentages were calculated based on the responses against each specific theme. Results revealed that majority of teachers performed academic activities which were based on teaching subject contents related to environment, social and economic sustainability. Regarding non-academic areas majority of teachers conducted activities such as cleaning of self and nearby environment; organizing competitions among students; providing vocational training and preparing useful materials from waste. Various initiatives such as inspiring and creating awareness among students; innovative pedagogical practices and activities on economic awareness were taken by the teachers in order to promote ESD.